Climate security risks in Kenya - Gadeberg, Marianne; Mascarenhas, Martina; Pacillo, Grazia; Taiwo, Ibukun (2023)
Climate change poses significant threats to Kenya’s agriculture, food security, peace, and security. Longstanding engagement with national authorities has allowed researchers from the CGIAR Climate Resilience Initiative (ClimBeR) to inform Kenya’s new National Climate Action Plan III as well as County Climate Change Action Plans, ensuring that climate security issues are included and addressed. A training course under development with the Climate-Smart Agriculture Multi-Stakeholder Platform (CSA-MSP) will demonstrate how climate-smart agriculture can be used as a tool for peace.